2003
DOI: 10.2460/javma.2003.222.1399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shedding of bovine herpesvirus 1, bovine viral diarrhea virus 1, and bovine viral diarrhea virus 2 after vaccination of calves with a multivalent modified-live virus vaccine

Abstract: Shedding of BHV1, BVDV1, and BVDV2 after vaccination was either nonexistent or undetected and did not result in transmission of BHV1, BVDV1, or BVDV2 vaccine viruses to pregnant contact control cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
(5 reference statements)
0
18
0
Order By: Relevance
“…Treatments were not arranged spatially according to vaccination treatment; because of random treatment assignment, there were instances where vaccinated and nonvaccinated calves had fence-line contact during the study. However, using the same RESP vaccine as in the current study, Kleiboeker et al (2003) concluded that shedding of BVDV type I or II in calves after vaccination was nonexistent or undetected and did not result in transmission of either BVDV genotype in pregnant contact control cows.…”
Section: Methodsmentioning
confidence: 53%
“…Treatments were not arranged spatially according to vaccination treatment; because of random treatment assignment, there were instances where vaccinated and nonvaccinated calves had fence-line contact during the study. However, using the same RESP vaccine as in the current study, Kleiboeker et al (2003) concluded that shedding of BVDV type I or II in calves after vaccination was nonexistent or undetected and did not result in transmission of either BVDV genotype in pregnant contact control cows.…”
Section: Methodsmentioning
confidence: 53%
“…The results indicated that titers of antibodies against BHV-1 and BVDV type 2 in the blood of vaccinated cows at approximately 5 weeks after their initial vaccine injection were significantly elevated, compared with those antibody titers in unvaccinated control cattle. 29 Although it is possible that, when not lactating, some of the study cattle came into contact with recently vaccinated lactating cattle that were shedding the virus, it seems unlikely that the anti-BVDV type 1 antibody titers detected in the present study resulted from such contact. On the day of parturition (within 12 hours after calving), there were also significantly higher titers of antibodies against BHV-1 and BVDV type 2 in the colostrum of vaccinated cattle, compared with findings in unvaccinated cattle.…”
Section: Discussionmentioning
confidence: 71%
“…The control calves and contacts with vaccinates remained seronegative though out the study. While a transient viremia (cell culture positive) and blood positive by PCR occurred after vaccination, there was no evidence of viral shedding [36]. If virus is found in MLV vaccinates, the detection of MLV strains in calves' nasal secretions receiving parenteral vaccines by label route does not mean calves are capable of infecting other animals.…”
Section: Discussionmentioning
confidence: 95%
“…One study administered a MLV vaccine containing BoHV1, BVDV1a and BVDV2a to seronegative calves. Unvaccinated control calves (in a separate pen) were included along with pregnant cows housed with vaccinates [36]. Nasal swabs and peripheral blood was collected through day 42.…”
Section: Discussionmentioning
confidence: 99%